Optimization of Expression Matching for String Matching - Tianlong Yang; Hongli Zhang (Dianxin kexue)
As the requirement of network security application increases, more and more redundant patterns appear and the patterns' amount of intrusion detection system（IDS）raises. The redundant patterns affect the coefficient of utilization of system's resource, and the performance of IDS directly. The inclusion relationship for expression was classified, and the algorithms eliminating redundant expressions were proposed. Then, to optimize the BitCount algorithm, a theoretical O（1）algorithm（MaskVeri）for mask verification was designed. The experimental result shows that MaskVeri performs better than other programming realization.